AR with cloud anchors: a way to improve HCI and interactive art - Antunes, João (2019)
Despite all the potential of augmented reality to improve the human-computer interface (HCI) and the user experience, it’s still below the expected usage. The reason may be related to the fact that until recently the AR implementation was mostly markerbased or GPS-based to trigger additional content (video, 3D, or other) to the reality identified with the camera. The research in this paper is focused on AR marker-less solutions that allows sharing AR content between users across the Cloud, based on the anchor identification. With this technological paradigm shift, the potential for use of new functional environments and an unprecedented status of HCI enrichment is achieved. In addition to the operations related to the applications functionality, the door opens for media-art artists to create AR models that can be shared in a multiple user environment across the Cloud.